Household Costs of Leprosy Reactions (ENL) in Rural India - Chandler, David J. (PLoS Negl Trop Dis, 2015)
BACKGROUND: Erythema nodosum leprosum (ENL) is a common immune-mediated complication of lepromatous (LL) and borderline lepromatous (BL) leprosy. Most patients experience chronic or multiple acute ENL over many years during an economically active period of their lives. Understanding the economic burden of ENL is essential to provide effective patient support, yet this area has not been investigated. METHODS: Ninety-one patients with LL or BL leprosy attending a leprosy hospital in Purulia district of West Bengal, India, were interviewed using a structured questionnaire. Cases (n = 53) were identified as those who had one or more episodes of ENL within the last 3 years. Controls (n = 38) had LL or BL leprosy but no history of ENL. Data were collected on household income, direct and indirect costs, and coping strategies. FINDINGS: The total household cost was Rs 1543 per month or 27.9% (IQR 13.2-52.6) of monthly household income for cases, and Rs 237 per month or 4.9% (IQR 1.7-13.4) of monthly household income for controls. Indirect costs accounted for 65% of total household costs for cases. Direct costs accounted for the remaining 35% of household costs, and resulted almost entirely from treatment-seeking in the private sector. Total household costs exceeded 40% of household income for 37.7% of cases (n = 20) and 2.6% of controls (n = 1) [1 USD = 59 INR]. INTERPRETATION: Households affected by ENL face significant economic burden and are at risk of being pushed further into poverty. Health policy should acknowledge the importance of private sector provision and the significant contribution to total household costs of lost productivity (indirect cost). Further work is needed to explore this area and identify solutions.